WHEN STATES LOSE TERRITORY: GEORGIA‘S POST-2008 ADJUSTMENT - Jakniūnaitė, Dovilė (Baltic Journal of Political Science, 2018)
In this article I analyse how Georgia, as a political entity, coped with the de facto loss of two of its territories: Abkhazia and South Ossetia. The process by which Georgia lost these territories started in early 1990 and reached its final phase in 2008 after the Georgian-Russian war. This article explores how Georgia adjusted to these losses without ever acknowledging its loss of the two territories, demonstrating a perfect example on how the normative territorial structure of an international system works. The analysis focuses on the crucial role of time in the process of the de facto territorial changes and examines how Georgia, in adapting to territorial losses and through its own actions, actually strengthened its separation from Abkhazia and South Ossetia.